The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1678-457x.10115
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive fractions from cantabrian anchovy (Engraulis encrarischolus) viscera

Abstract: The potential of cantabrian anchovy (Engraulis encrarischolus) viscera as a source of bioactive compounds is of interest for both, pharmaceutical and food industries. Cantabrian anchovy guts and heads were freeze-dried, extracted with methanol and subjected to fractionation by solvent partitioning using hexane, ethyl acetate, and butanol. Fractions were tested for antimutagenic, antioxidant, antifungal, and antibacterial activity using the Ames test; DPPH, ABTS, and FRAP assays; the radial grown inhibition ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…According to Burgos-Hernández et al [23] and Ramos-Hernández et al [10], the composition of the primary level of the extract, prevents HBVC from fully expressing their biological effects. Hence, a separation into fractions by column chromatography is required.…”
Section: Fractionation Of Extract By Column Chromatography and Qualit...mentioning
confidence: 99%
“…According to Burgos-Hernández et al [23] and Ramos-Hernández et al [10], the composition of the primary level of the extract, prevents HBVC from fully expressing their biological effects. Hence, a separation into fractions by column chromatography is required.…”
Section: Fractionation Of Extract By Column Chromatography and Qualit...mentioning
confidence: 99%
“…Suárez-Jiménez et al (2015) reported that collagen hydrolysates from jumbo squid by-products exhibited an effective inhibition of the induced mutation with AFB 1 of S. typhimurium TA98 and TA100 strains. Additionally, Burgos-Hernández et al (2016) investigated the antimutagenic potential of several fractions obtained from anchovy viscera against AFB 1 using S. typhimurium TA98 and TA100 tester strains. Dn the other hand, several studies reported the antimutagenic activity of some compounds obtained from seafood products such as white shrimp (López-Saiz et al, 2016), octopus (Cruz-Ramírez et al, 2015), and some other marine resources such as several species of seaweed (Dsuna-Ruiz et al, 2016).…”
Section: Antimutagenic Activitymentioning
confidence: 99%
“…Lately, there is a particular interest in researching the antioxidant activity of fish viscera, e.g., Abdelhedi et al (2017) had obtained low molecular weight (MW) peptide (<1 kDa) by the ultrafiltration from smooth hound viscera protein hydrolysates and the peptide exhibited good antioxidant capacity. Burgos-Hernandez et al (2016) investigated bioactive fractions from cantabrian anchovy ( Engraulis encrarischolus ) viscera and the fractions showed the antioxidant activity through various assays. In addition, there were many other studies on fish viscera protein hydrolysates ( Villamil, Vaquiro & Solanilla, 2017 ).…”
Section: Introductionmentioning
confidence: 99%